Rumah Adat Balla Lompoa Kakaraengang Marusu Kassi Kebo di Kabupaten Maros (Suatu Kajian Historis) - Rachmah, ST (Phinisi Integration Review, 2018)
In south Sulawesi, particularly in Maros district, there is one of traditional house known as Balla Lompoa which is located in Kassi Kebo in Maros district. The traditional house is one of heritage of Marusu King which still stands firmly and is maintained well by the descendants of the king who are still alive and the local government, and becomes one of tourists’ destinations in Maros district, besides other places interest such as Leang-leang and Bantimurung. The research aims to discover the historical background of Marusu Kingdom in Maros district, the condition of Balla Lompoa Kakaraengang Marusu Kassi Kebo traditional house in Maros district, and the role and function of Balla Lompoa was descriptive historical research which employed qualitative approach. The qualititative approach and analysis technique was conducted in for stages. The results of the research reveal that (1) the history of Marusu Kingdom was started with Tumanurung concept with the first King was Karaeng Loe ri Pakere and the last king was Andi Muhammad Tajudding daeng Masiga (1944-1963). As time went by, the government system in Maros was also developed and experienced the changes. “Gementschap Culture” was formulated in a form of “District”, (2) Balla Lompoa Traditional House was the Palace of Marusu Kingdom which also became hundreds of years old and is one of cultural heritages needed to be preserved in Maros district and has a collection of 300 kinds of King’s relics and Kakaraengang Marusu, (3) the role of Balla Lompoa Kassi Kebo traditional house is not only as the facility for the implementation of traditional ceremony or as the residence of Karaeng and his family, but also a place for holding a meeting for the royal family.